UNIQUE ASPECTS OF MILITARY PERSONNEL HEALTH AND METABOLIC SYNDROME RISK FACTORS (World Bulletin of Public Health, 2026)
Metabolic syndrome (MetS) represents a significant public health challenge characterized by the coexistence of central obesity, hypertension, dyslipidemia, and impaired glucose metabolism, substantially increasing the risk of cardiovascular diseases and type 2 diabetes. Military personnel constitute a unique occupational group exposed to specific health stressors, including chronic psycho-emotional stress, intense physical demands, irregular work-rest cycles, sleep deprivation, suboptimal dietary patterns, and environmental challenges. These factors collectively create a favorable background for the development of metabolic disturbances.